Three new species of pseudoscorpions (Arachnida: Pseudoscorpiones: Pseudotyrannochthoniidae) from caves in Yunnan and Guizhou Provinces, China - Li, Yun-Chun (European Journal of Taxonomy, 2023)
Three new species of pseudoscorpion, Allochthonius lini sp. nov. (Xiaoguoquan Cave) and Selachochthonius yinae sp. nov. (Xiao Cave) from Yunnan Province, Allochthonius xuae sp. nov. (Yelaoda Cave) from Guizhou Province, are described and illustrated. An identification key is provided for all known Chinese representatives of the family Pseudotyrannochthoniidae.